The Potential Role of Platelet - rich Plasma in the Treatment of Melasma (International Journal of Psychosocial Rehabilitation, 2020)
Objective: To evaluate the response of patients with melasma to intradermal injection of platelet-rich plasma. Background: Melasma is a frequently acquired disorder of hyperpigmentation that is characterized by asymptomatic light to dark brown patches on the face involving the forehead, cheeks, chin, and upper lip. In spite of several treatments for melasma, such as topical agents, chemical-based peeling, and laser and light source therapies, the treatment results are variable, with complications such as irritation, post-inflammatory hyperpigmentation, or hypopigmentation. Nonetheless, platelet-rich plasma (PRP) is getting attention in aesthetic medicine because of its autologous nature and mild side effects compared to other melasma treatments. Methods: The present study included 30 patients with melasma having Fitzpatrick skin types III and IV. The duration of the study extended from February to November 2019. The therapeutic course consisted of 5 sessions of platelet-rich plasma (PRP) injections with an interval of 2 weeks between them. PRP was prepared by using a double-spin method and then activated with calcium chloride. The final evaluation was analyzed by percent of reduction in baseline of mMASI score. It's considered a mild response when the reduction of the baseline mMASI was between 0 and 25%; a 25-50% reduction is considered a fair response; a 50-75% reduction is considered a good response; and >75% is considered an excellent response. The treatment trial was considered effective if there was a reduction in the mMASI score from the baseline that was greater than 50%. Results: Of 30 enrolled patients, 5 (16.7%) patients showed good response, 19 (63.3%) patients showed fair response, and 6 (20%) patients showed poor response. None of the patients showed an excellent response. The overall efficacy of treatment was 16.7%. Conclusion: PRP appears to be a promising adjuvant therapy for recalcitrant cases of melasma.